Responsibility to Protect: Implementing a Global Norm towards Peace and Security - An Interview with Dr Simon Adams; Global Centre for the Responsibility to Protect - Königs, Tomas; Nozawa, Junko; Teeuwen, Erica (Utrecht Journal of International and European Law, 2013)
In September 2000, as a result of growing critique and scepticism towards humanitarian intervention, UN Secretary-General Kofi Annan posed the following question to the international community: 'If humanitarian intervention is, indeed, an unacceptable assault on sovereignty, how should we respond to a Rwanda, to a Srebrenica - to gross and systematic violations of human rights that offend every precept of our common humanity?' In response to this challenge, the newly founded International Commission on Intervention and State Sovereignty ('ICISS'), introduced a new approach towards humanitarian intervention in its final report: the Responsibility to Protect ('R2P'). Concisely, the R2P principle holds that the responsibility to protect people in a state from severe human rights violations shifts to the international community when that respective state fails to live up to said responsibility. Although the R2P principle has received general acceptance by the international community, it is not just individual states that play a role in ensuring the implementation of doctrine. Various international organisations have established themselves as authoritative bodies that contribute to the advancement and institutionalisation of the R2P norm through international advocacy and extensive research. In this interview, Executive Director of the Global Centre for the Responsibility to Protect Dr Simon Adams shares his views on the development of the R2P principle in light of recent human rights atrocities.